Optimalisasi Penggunaan Sosial Media Sebagai Media Pemasaran Digital Bagi Siswa SMAN 1 Tualang - Syintia Mega Putri Syintia; Figo Alimbel; Ivan Chatisa (JIPITI: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to optimize the use of social media as a digital marketing medium for students of SMAN 1 Tualang. The implementation method used a workshop approach consisting of three stages: preparation, implementation, and evaluation. The activity was conducted on August 28, 2025, at the Computer Laboratory of SMAN 1 Tualang, involving 40 students and 6 accompanying teachers. The workshop materials included content marketing strategies, utilization of various social media platforms, audience engagement techniques, and live streaming practice using OBS Studio. The results showed a significant increase in students' understanding of digital marketing concepts, from an average pre-test score of 45% to 78% in the post-test. Student enthusiasm was evident from active participation during material presentations and numerous questions during discussion sessions. Survey results indicated that TikTok and Instagram were the preferred platforms for youth marketing with 68.4% preference each. This activity successfully enhanced students' knowledge and skills in utilizing social media platforms productively and strategically for digital marketing purposes.